Premature loss of primary teeth in children aged 4 to 8 who attend the Central University of Ecuador - Espín Flores, María (2021)
Objective: to determine the frequency of early loss of deciduous teeth in children aged 4 to 8 who attended the Central University of Ecuador. Methodology. The sample consisted of 453 medical records of patients who were seen from March 2017 to April 2018. The following data were recorded: age, gender, premature tooth loss, diagnosis of the missing tooth and whether the space maintainer was performed. Descriptive statistics and the Welch Levene and ANOVA tests were performed with a significance level of 5% (p <0.05). Results. The frequency of premature loss of primary teeth was 56.5%. no statistical differences between gender and age. The lower left second molar was the tooth with the greatest premature loss (7.3%). The space maintainer was performed in 30% of the cases. There were no statistically significant differences by gender and age. Conclution. Early loss of deciduous teeth was high for the group studied. Space maintainer realization was low. The implementation of educational and preventive programs to promote oral health can help children maintain healthy primary teeth and prevent alterations in the development of occlusion.